Audience Development Strategy in the Theatre - Essien, Edet (Program Studi Sosiologi, 2020)
The position of arts patrons is that of importance. The audience is the reason why the artist is there. Without their presence, the theatre experience is incomplete. This work examines the different categories of audiences that exist and the audience development strategies often employed. It identifies that the development of audiences for the theatre is prosecuted at two different but related levels; the first focuses on attracting attention to the event while the second gears towards sustaining the interest so generated. These issues are pertinent and vital and should be considered if theatre is to thrive, especially in this era where it is in serious competition with other modes.